2010
DOI: 10.4238/vol9-2gmr726
|View full text |Cite
|
Sign up to set email alerts
|

GSTT1, GSTM1, and GSTP1 polymorphisms and chemotherapy response in locally advanced breast cancer

Abstract: ABSTRACT. The glutathione S-transferase (GST) family consists of phase II detoxification enzymes that catalyze the conjugation of toxic substances, such as chemotherapeutic agents, to glutathione. We examined whether GSTT1/GSTT1"null", GSTM1/GSTM1"null" and GSTP1Ile105Ile/GSTP1Ile105Val polymorphisms are associated with different response rates to neoadjuvant chemotherapy in the treatment of stage II and III breast cancer. Forty Brazilian women with invasive ductal adenocarcinoma of the breast submitted to neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 30 publications
0
32
1
Order By: Relevance
“…The GST has been shown to have activity both by direct detoxification of the drugs themselves or through detoxification of lipid hydro peroxides generated by the cytotoxic drugs [12]. In addition, the GSTs are also involved in cell signaling pathways that control stress response, apoptosis, and cellular proliferation [13]. Thereby, the polymorphisms in the genes of these enzymes could contribute to tumor cell survival and drug resistance by causing detoxification of products of cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The GST has been shown to have activity both by direct detoxification of the drugs themselves or through detoxification of lipid hydro peroxides generated by the cytotoxic drugs [12]. In addition, the GSTs are also involved in cell signaling pathways that control stress response, apoptosis, and cellular proliferation [13]. Thereby, the polymorphisms in the genes of these enzymes could contribute to tumor cell survival and drug resistance by causing detoxification of products of cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…As only a part of the HPV infected women develop precancerous cervical lesions or cancer, prophylactic evaluation of GST family enzymes could play a major role in identifying high risk individuals for an efficient therapeutic interference, here including HPV vaccination (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies in Chinese breast cancer patients. Only several studies conducted in western countries investigation the association of GSTs with chemotherapy response and survival of breast cancer, but the results are conflicting (Satta et al, 1992;Whelan et al, 1992;Ott et al, 2008;Lourenço et al, 2010;Oliveira et al, 2010;Mishra et al, 2011). A study conducted in Brasil showed combination of null GSTT1 and GSTP1 105Val have poor response than combination of non-null GSTT1 and GSTP1 105IIe (Oliveira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Only several studies conducted in western countries investigation the association of GSTs with chemotherapy response and survival of breast cancer, but the results are conflicting (Satta et al, 1992;Whelan et al, 1992;Ott et al, 2008;Lourenço et al, 2010;Oliveira et al, 2010;Mishra et al, 2011). A study conducted in Brasil showed combination of null GSTT1 and GSTP1 105Val have poor response than combination of non-null GSTT1 and GSTP1 105IIe (Oliveira et al, 2010). However, another study in Indian, it did not find a significant association between glutatinione S-transferases and responses to chemotherapy (Mishra et al, 2011), and another study conducted in Germany did not found a significant responses to chemotherapy among individuals with GSTT1, GSTM1 and GSTP1 (Ott et al, 2008).…”
Section: Discussionmentioning
confidence: 99%